The cruelty is the point [large type] : the past, present, and future of Trump's America - Serwer, Adam (Random House Large Print, 2021)
"Taking joy in suffering is more human than we'd like to admit. The cruelty of the Trump administration's policies and the ritual rhetorical flaying of his targets are intimately connected. Shared cruelty and the delight it brings are critical moments of connection for white supremacists, a fact that is not new. Adam Serwer has been chronicling our political landscape for the last decade. But this collection isn't just about Trump--it's an investigation across centuries interrogating both this moment and its antecedents to reveal the deep roots that have given rise to Trumpism. New material includes four, audience-building essays that expand upon the collection's themes, and unearth more approaches to nationalism and pluralism. Like the polarizing effect Trump's administration has had on American Jews; tracing the emergence of police unions; and making the historical case for abolishing billionaires to preserve American democracy"--